Enforcing data protection - assessing the challenges the right to be forgotten faces - Kökkö, Kasperi (My University, 2023)
Technologies gathering personal data and the immortality of that data have raised concerns regarding the respect for the private life of an individual, which has created the need for developments in the field of data protection. One of the most controversial additions to data protection has been the introduction of an explicit right to be forgotten. Such an addition highlights the importance of the right to privacy, but on an international level, a consensus regarding the balance of fundamental rights has been difficult to reach, creating an environment where the level of protection guaranteed to individuals, as well as obligations to data controllers, vary depending on the regulation applied. In this thesis, the restrictions imposed by the doctrine of jurisdiction on the effective functioning of an explicit right to be forgotten are discussed. Should an explicit right to be forgotten exist effectively, it must pass the obstacles that its enforcement faces. This thesis is a socio-legal analysis. Consequently, the doctrine of jurisdiction is not viewed only as a set of rules that govern the actions of States, but as a concept affected by the constant changes in our society. Furthermore, the right to be forgotten itself is seen rather unstable and vulnerable to the influence of ideological changes around the world. According to the findings in this thesis, although restrictions and incompatibilities with traditional interpretations of jurisdiction are detected, the explicit right to be forgotten is not deemed as redundant as its enforcement in practice is not purely dependent on the possibilities of enforcement derived from the traditional interpretations of the rule of law, but also affected by the voluntary compliance of online actors and technological developments.

Henkilötietoja keräävien teknologioiden ja näiden henkilötietojen kuolemattomuuden vaikutukset oikeuteen yksityisyyden kunnioittamiseen ovat herättäneet huolia, mikä on luonut tarpeen tietosuojalainsäädännön kehittämiselle. Yksi kyseenalaisimmista lisäyksistä tietosuojalainsäädäntöön on ollut nimenomainen oikeus tulla unohdetuksi. Kyseinen lisäys korostaa yksityisyydensuojan merkitystä, mutta kansainvälisellä tasolla tasapainon löytäminen eri perusoikeuksien välille on ollut haastavaa. Tämä on luonut ympäristön, jossa eri lainsäädännöt tarjoavat sekä eritasoista suojaa yksilöille että erisisältöisiä velvollisuuksia rekisterinpitäjille. Tässä tutkielmassa käsitellään niitä rajoituksia, joita kansainvälisen oikeuden lainkäyttö- ja täytäntöönpanovaltojen opit asettavat tietosuojalainsäädännön, tarkemmin oikeuden tulla unohdetuksi, tehokkaalle toimimiselle. Jotta oikeus tulla unohdetuksi voisi toteutua tarkoitetulla tavalla, sen on pystyttävä selvittämään ne haasteet, joita sen täytäntöönpano kohtaa. Tämä tutkielma on oikeussosiologinen tutkimus. Näin ollen lainkäyttö- ja täytäntöönpanovallan oppeja tulkitaan konsepteina, joiden tulkinta on alttiina yhteiskunnassa jatkuvasti tapahtuville muutoksille, eikä ainoastaan joukkona sääntöjä, jotka sääntelevät valtioiden toimintaa. Lisäksi oikeus tulla unohdetuksi nähdään verrattain epävakaana ja niin ikään alttiina ideologisten muutosten vaikutukselle. Tutkielman johtopäätösten mukaan nimenomainen oikeus tulla unohdetuksi ei muodostu tarpeettomaksi vain sen takia, että kansainvälisen oikeuden täytäntöönpanovaltaopin perinteiset tulkintatavat aiheuttavat rajoituksia sen täytäntöönpanolle. Käytännössä täytäntöönpano ei katso vain niitä mahdollisuuksia, joita perinteiset täytäntöönpanovallan opit tarjoavat, vaan myös sääntelyn kohteena olevien toimijoiden vapaaehtoinen sääntelyn noudattaminen sekä kehitykset teknologiassa vaikuttavat oikeuden tulla unohdetuksi tosiasialliseen toteutumiseen.
Keywords: personal data, data protection, jurisdiction, enforcement jurisdiction, right to be forgotten, henkilötiedot, tietosuoja, toimivalta, täytäntöönpanotoimivalta, oikeus tulla unohdetuksi